The microtubule targeting agent PBOX-15 inhibits integrin-mediated cell adhesion and induces apoptosis in acute lymphoblastic leukaemia cells - Mc Elligott, Tony (My University, 2013)
Although recent decades have seen an improved cure rate for newly diagnosed paediatric acute lymphoplastic leukemia (ALL), the treatment options for adult ALL, T-cell ALL (T-ALL) and relapsed disease remain poor. We have developed a novel series of pyrrolo-1,5-benzoxazepine (PBOX) compounds and established their anti-cancer efficacy in a variety of human tumour cells types. Here, we demonstrate that PBOX-15 inhibits cell growth, and induces G2/M cell cycle arrest and apoptosis in both T-ALL and B-cell ALL (B-ALL) cells. In addition, prior to PBOX-15-induced apoptosis, PBOX-15 decreases ALL cell adhesion, spreading and migration. Concurrently, PBOX-15 differentially down-regulates B1-, B2- and ?4-integrin expression in ALL cells and significantly decreases integrin-mediated cell attachment. PBOX-15 interferes with the lateral mobility and clustering of integrins in both B-ALL and T-ALL cells. These data suggest that PBOX-15 is not only effective in inducing apoptosis in ALL cells, but also has the potential to disrupt integrin-mediated adhesion of malignant lymphocytes, which represents a novel avenue for regulating leukemic cell homing and migration.
PUBLISHED
Keywords: leukaemia cells; Cancer